Management of pregnancy for a patient with the new syndromic macrothrombocytopenia, DIAPH1-related disease. (3rd October 2018) - Nurden, Paquita; Nurden, Alan; Favier, Rémi; Gleyze, Matthieu
Abstract: The number of genes involved in the identification of macrothrombocytopenia (MTP) is growing but the clinical consequences for the affected patients are not well determined. Here, we report the management of the bleeding risk for a patient with the newly reported and rare DIAPH1-related disease during surgery for infertility and then during her subsequent pregnancy. The R1213* DIAPH1 variant responsible for a mild bleeding syndrome in six families was considered a potential risk factor for our patient. Preliminary laparoscopic surgery was followed by neosalpingostomy to open the obstructed fallopian tube that was followed by an ectopic pregnancy requiring further surgery, tranexamic acid was used on each occasion and no bleeding complications were observed. A second pregnancy proceeded to term; the mother's platelet count was controlled throughout the gestation period and remained close to her basal values. No bleeding occurred at delivery or during the postpartum period. In conclusion, with strict repeated assessments of blood parameters and maintenance of the platelet count, the bleeding risk in pregnancy in DIAPH1-related disease can be successfully controlled.